Exploration on the Optimal Application of Mobile Cloud Computing in Enterprise Financial Management under 5G Network Architecture - Yanlin Guo; Huwei Li (Advances in Multimedia)
In order to improve the effect of modern enterprise financial management, this paper improves the mobile cloud computing resource scheduling algorithm under the 5G network architecture. Moreover, this paper introduces mobile edge cloud computing, MEC server, into the financial 5G network system model. Taking into account the possible multihop RSU transmission of the calculation result back, this paper expresses the delay composition of the calculation task on the local execution and offloading to the MEC server in the form of a formula and proposes an offloading strategy based on the MEC load status. On this basis, this paper constructs a mobile cloud computing optimization system under the 5G network architecture and designs experiments to evaluate the performance of the system proposed in this paper. From the experimental research, we can see that the enterprise financial management optimization system based on mobile cloud computing under the 5G network architecture proposed in this paper has good effects in the optimization of corporate financial management.